Squeezing red blood cells on an optical waveguide to monitor cell deformability during blood storage. Issue 1 (13th November 2014) - Ahluwalia, Balpreet Singh; McCourt, Peter; Oteiza, Ana; Wilkinson, James S.; Huser, Thomas R.; Hellesø, Olav Gaute
Abstract : Red blood cells squeeze through micro-capillaries as part of blood circulation in the body. Abstract : Red blood cells squeeze through micro-capillaries as part of blood circulation in the body. The deformability of red blood cells is thus critical for blood circulation. In this work, we report a method to optically squeeze red blood cells using the evanescent field present on top of a planar waveguide chip. The optical forces from a narrow waveguide are used to squeeze red blood cells to a size comparable to the waveguide width. Optical forces and pressure distributions on the cells are numerically computed to explain the squeezing process. The proposed technique is used to quantify the loss of blood deformability that occurs during blood storage lesion. Squeezing red blood cells using waveguides is a sensitive technique and works simultaneously on several cells, making the method suitable for monitoring stored blood.